SOME PROBLEMS OF BIAS IN MAILED QUESTIONNAIRES - Repar, George William (My University, 1963)
The purpose of this investigation is to analyse some of the objective differences between individuals who reply to self-administered mail questionnaires and those who do not. Since studies have shown that the rate of returns to mailed questionnaires varies between twenty percent to seventy percent, the question of who replies to a mail questionnaire requires further attention. Easly research assumed that it was simply a matter of chance whether one individual or another answered mailed questionnaires, however, various investigators2 soon began to doubt the validity of this assumption. Current research makes it quite clear that mail questionnaires are only reaching certain types of respondents. Thus Franzen and Lazersfeld write: "Mail questionnaires are answered more often by people who, due to their educational and occupational background more easily express themselves in writing than by people who are more interested in the topic under discussion” The present study continues this type of investigation and attempts an examination of four related problems. We would like to know: (a) The social and demographic factors which allegedly distinguish repliers from non-repliers to self-administered mail questionnaires. (b) Whether an individual’s educational level is a primary variable which differentiates between respondents and non-respondents. (c) Whether the content of the questionnaire influences the rate of returns. (d) Whether the rate of questionnaire returns is effected by one specific variable of this study - "college intentions of the student”
Keywords: questionnaire; sociology